Taking the human body seriously. Issue 1 (2nd January 2021) - Chughtai, Hameed
ABSTRACT: The intention of this article is to open up a dialogue on the importance of giving explicit attention to the human body when studying information systems phenomena. The human body influences the ways in which a person interprets and uses technology. Although we bodily engage with our world (people, things and places), we generally take our bodies for granted, and view them as passive recipients in studies on information technologies and organisational phenomena. Theoretical frameworks built on embodiment indicate that human beings are embedded in their social context, but they do not often include the human body with its somatic aspects (such as orientation, position and movement). Using a theoretically informed ethnographic case, I draw attention to how the human body affects the ways in which we interpret and use technology. The findings suggest revisiting the idiosyncratic view of human embodiment, which often overlooks somatic orientations and modes of engagement. The article contributes a theoretical framework relevant for inquiry into the structure of somatic practices in information systems. I conclude with a discussion of the implications for theory and practice.